Female Neuregulin 1 Heterozygous Mice Require Repeated Exposure to Δ9-Tetrahydrocannabinol to Alter Sensorimotor Gating Function - Spencer, J. R.; Chohan, T. W.; Karl, T.; Arnold, J. C. (Pharmacopsychiatry, 2013)
The schizophrenia susceptibility gene neuregulin 1 (NRG1) confers vulnerability to the neurobehavioural effects of cannabinoids differently across sexes. Male but not female Nrg1 heterozygous (HET) mice display facilitation of prepulse inhibition (PPI) to acute Δ9-tetrahydrocannabinol (THC) exposure compared to WT controls. We aim to observe whether repeated administration of THC may overcome the acute insensitivity of female Nrg1 HET mice to THC exposure.Female Nrg1 HET mice and WT controls were administered THC daily for 21 days, with PPI and anxiety-related behaviour in the light-dark test (LD) examined on the first and last day of treatment and 21 days after cessation of dosing.Following repeated, but not acute THC exposure, female Nrg1 HET mice displayed THC-induced facilitation of PPI which was not observed in WT mice treated with THC. There were no residual effects of THC on PPI in either genotype when assessed 21 days following the final THC dose. An anxiogenic response to THC was evident following repeated, but not acute, administration in the LD test in both genotypes.These findings show that the acute insensitivity of female Nrg1 HET mice to THC-induced PPI facilitation may be overcome following repeated THC exposure.
Keywords: schizophrenia; neuregulin 1; animal model; cannabis; prepulse inhibition